Longitudinal association between cognitive performance and obsessive-compulsive symptoms in patients with psychosis and unaffected siblings - Schirmbeck, Frederike; Zink, Mathias (Acta psychiatrica Scandinavica, 2016)
Objective Obsessive-compulsive symptoms (OCS) frequently occur in psychotic disorders. Cross-sectional associations between OCS and cognitive impairment have led to different causal explanations. Whereas one assumes that higher cognitive impairment reflects a risk factor for psychotic patients to develop OCS, another suggests that deficits reflect a consequence of OCS. This study investigated the longitudinal interrelation between OCS and cognitive functioning. Method Baseline and follow-up data from 622 patients and 670 un-affected siblings from the ‘Genetic Risk and Outcome in Psychosis’ study were analyzed. Participants were allocated to groups according to the presence or absence of OCS at assessments and compared on several cognitive domains. Results Cross-sectional comparisons revealed no group differences in cognitive performance. Longitudinal analyses comparing the groups with changes in OCS revealed one significant group effect with more problems in set-shifting abilities in patient who reported OCS development at follow-up. Significant time and interaction effects were mainly due to improvement in immediate verbal recall and digit-symbol coding in patients and siblings who reported remission of OCS. Conclusion Although insight into causality needs further exploration, our results do not confirm the hypothesis of pre-existing cognitive risk constellations. Findings suggest that remission of comorbid OCS results in improved immediate verbal recall and processing speed.
Gesehen am 17.05.2019